Boosting Infant Growth: Exploring the Influence of Baby Massage on Weight Gain in 1-6 Month-Olds - Lailaturohmah, Lailaturohmah; Soya Nita, Elin; Merita Sari, Pety (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Massage therapy is one of the oldest healing methods worldwide, encompassing both healthcare and treatment. Baby massage offers numerous benefits, including the enhancement of infant weight gain. In Kediri, East Java, child growth and development issues persist, with a prevalence of underweight children at 17.5% and wasted children at 9.0%. This research aims to analyze the impact of baby massage classes on infant weight gain. This study adopts a quasi-experimental design with a Two Group Pretest-Posttest format. The research subjects were divided into two groups: control and treatment. Pretest and posttest measurements were conducted. Statistical analysis using paired t-tests yielded a significance level of p=0.000 (p<0.05), indicating a significant influence of baby massage classes on weight gain in infants aged 1-6 months. The average weight gain after intervention was 5200 grams.Of the total respondents, 19 infants (63.3%) experienced weight gain, with 13 from the intervention group and 6 from the control group. However, 9 infants (30%) maintained their weight, with 2 from the intervention group and 7 from the control group, while 2 infants (6.7%) experienced weight loss, all from the control group.Baby massage classes have a positive impact on infant weight gain at the Ibu Hawa Clinic in Kediri Regency.